A Rare Case of Double Antibody-Positive Rapidly Progressive Glomerulonephritis: A Therapeutic Challenge - Stephen Bell MD; Natalia Lattanzio MD; Qassem Abdelal MD; Yeshanew Teklie MD; Talal Alkayali MD; Wilhelmine Wiese-Rometsch MD; Ashok Sastry MD (SAGE Publishing, 2021)
Crescentic glomerulonephritis, also known as rapidly progressive glomerulonephritis, is a syndrome characterized by progressive and rapid deterioration of renal function over the course of weeks to months. Oliguria, hematuria, azotemia, and hypertension are characteristic features of this condition. Crescentic glomerulonephritis is further classified according to the staining pattern on immunofluorescence. In rare instances, a mixed pattern of injury is encountered as in the case of double antibody-positive rapidly progressive glomerulonephritis (RPGN). This case illustrates the challenge in treatment of double antibody-positive RPGN in an elderly female with no previous renal disease. The patient was found to be positive for anti-GBM antibody and MPO-ANCA. Treatment was initially targeted against MPO-ANCA as the biopsy was most consistent with this process; however, the patient failed to respond to treatment and was subsequently transitioned to oral cyclophosphamide directed against anti-GBM disease. In cases of doubly antibody-positive RPGN with anti-GBM disease and ANCA-associated vasculitis, initial treatment should focus on inducing remission of anti-GBM disease as double antibody-positive disease often presents with the aggressive morbidity and mortality seen in anti-GBM disease, and the chronic risk of relapse seen in ANCA-mediated vasculitis.